Allelopathy Potential of Alpinia malaccensis (Burm. F.) Roxb. due to Seeds Germination and Growth of Merremia peltata (L.) Merril - Siti Aisah; Sulistijorini Sulistijorini; Titiek Setyawati (Journal of Tropical Life Science, 2018)
Allelopathy is a natural strategy for the protection or inhibition toward other vegetation through the release of chemicals into the environment. Alpinia malaccensis is thought to be capable of carrying out allelopathic mechanisms, as this species is found to grow well on land invaded by Merremia peltata. Invasive type control with alleopathic mechanism is an alternative to consider as it does not leave a potential residue as a contaminant of soil as it is chemically controlled. The study attempt to investigate the content of A. malaccensis allelochemicals and analyzed the alelopathy potential of A. malaccensis on seed germination and seedling growth of M. peltata. Research method used completely randomized design with 6 replicates for seed treatment and three replicates for seedling treatment. Seeds which have relatively similar size and weight were obtained from the field. Seeds were germinated in petri dishes that have been coated by filter paper, each petri dish contained 6 seeds of M. peltata. The treatment of the seeds germination was performed by giving 3 ml of rhizomes and leaves extracts of A. malaccensis (control, 30 g/L, 60 g/L, 90 g/L, 120 g/L, and 150 g/L). The treatment of the seedlings was performed by giving 30 ml of rhizomes and leaves extracts of A. malaccensis (control, 50 g/L, 100 g/L, 150 g/L, and 200 g/L). The analysis of chemical compounds of fresh rhizomes and leaves showed that A. malaccensis contains alcohol, amide, fatty acid, phenol, ketones, and terpenoids. Rhizomes and leaves extracts 150 g/L of A. malaccensis showed the highest inhibition in germination, dry weight, plumule and radicle length of M. peltata sprout parameters. Rhizomes and leaves extract 200 g/L of A. malaccensis showed the highest inhibition in tendril length, amount of leaves, length and width of M. peltata leaves parameters. To be more efficient, application in the field should use low concentration of extracts that can inhibit the M. peltata. Results of this study are expected to provide information about alternative solutions to suppress the invasion of M. peltata to preserve ecosystems of Bukit Barisan Selatan National Park (BBSNP) in Lampung.